Reproductive biology and behavior of Doru taeniatum (Forficulidae) - Briceño, R. Daniel; Schüch, Wolfganf (Revista de Biología Tropical, 1988)
This study deals with the biology of Doru taeniatum, (Forficulidae), particulary the habitat, feeding, reproduction, maternal care, and nymphal stages. The density of adults is higher in the older corn plants. The earwings were more often found at the top, where the leaves form a sheath in young plants. Corn fields are apparently colonized during the early stages of growth by males and females: this permits the development of a least one generation. Complex and sterotyped fights occur among males and the secondary sexual modifications of the cerci play an important role. During courtship, vibratory movements of the abdomen of the male were observed an many occasions. The power spectrum of the signal showed peaks at several frecuencies (5.4 Hz was the strongest) probably, the main function of these signals is to make the females more receptive during countship.